A survey of online and social media records management of frontline government offices in the Philippines - Torres, Andre Pocholo B. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
The study surveyed Philippine frontline government offices on their usage and management of online and social media records and identified the types of content posted, how they were managed and the issues surround their usage. The researcher then utilized existing social media records literature and Upward's Records Continuum model to develop a framework which identified key variables needed for the study.